COMPARISON OF VISUAL SHADE MATCHING ABILITY OF UNDERGRADUATE STUDENTS IN DIFFERENT LIGHTING CONDITIONS - KHAN, AA; ULLAH, H; KHAN, A; IQBAL, S; SHAHZADI, S; AYAZ, U (Biological and Clinical Sciences Research Journal, 2024)
Comparison of visual shades is essential in careers, such as dentistry since consistent color duplication is crucial for appearance. People have the skills to match shades in many aspects and lighting is among the most important factors that affect the versatility. Knowledge of how different lighting environments impact the ability of students to match shades visually can enhance educational approaches. Objectives: To compare the degree of the actual successful attempts of the subjects at the anatomic facial area and hair visual shade matching while being tested under different lighting conditions and superimpose the findings to determine the extent of influence of the conditions on the results. Methods: This descriptive cross-sectional study was conducted at the Department of Prosthodontics, Bacha Khan College of Dentistry from May 2024 to October 2024. The target population of this study was composed of three hundred undergraduate students and participants included one hundred and fifty students each undertaking visual shade-matching exercises under three distinct light sources; natural daylight, fluorescent, and LED lighting. Standardized shade tabs were used/ offered to the participants, who were asked to match them under those lighting. Accuracy data were collected, and thus analyses of the performances under various lighting conditions were made. The quantitative data variability was analyzed by using SD and p-value for statistical significance. Results: out of the 138 participants, those under natural daylight had the highest mean accuracy of 85.3% (SD ±5.4) out of 138 participants. Under fluorescent lighting, the percentage dropped to 78.1% (SD±6.1) with a higher standard deviation and highest error frequency. The application of LED lighting produced a mean accuracy of 82.7% (SD ± 5.9). Analysis of the result revealed that there was a statistically significant difference (p < 0.05) across all lighting conditions with natural daylight being preferable for shade matching. Conclusions: In particular, the findings reveal that identifying the correct shade under natural daylight is the best in comparison to other lighting conditions and those scores are worst under fluorescent light. Optimal lighting conditions used during the training can improve students’ learning performance in shade-matching tasks.